The Solubilities of Zn, Sb and Se Found in Anode Slime - Peker, Ibrahim (Asian Journal of Chemistry, 2010)
The purposes of the study were to examine the methods used for recovering the precious metals from the anode slime formed as a byproduct during the production of high purity copper by electrolytic means, and to investigate the products obtained. The characteristics of the electrolysed copper dictate the type and the amounts of Cu, Se, Te, Zn, Pb, Fe, Ni, Ag, Au and Pt group of metals present in the slime. Since the anode slime has a very low ratio of zinc by virtue, obtaining zinc from its ore is the best and most convenient way. The solubilities of Zn, Sb and Se present in an anode slime were examined by using sulphuric acid for the effects of the concentration of solvent, temperature and time. The increase in temperature and time (at 210ºC) increased the solubility of Se only and 80% of Se passed into the solution.